Investigation of functionally graded TPMS structures fabricated by additive manufacturing. (15th November 2019) - Yu, Shixiang; Sun, Jinxing; Bai, Jiaming
Abstract: Triply periodic minimal surfaces (TPMS), which have zero mean curvature and large surface areas, are discussed in this paper. Two TPMS structures, the Schwarz Primitive (P) and Gyroid, were designed with both uniform and graded density and fabricated using additive manufacturing (Stereolithography). The mechanical properties and energy absorption abilities of the printed TPMS samples were studied. The Schwarz P structure cracked layer by layer and exhibited obvious peak-valley stress feature during the compression test. The total absorbed energy to the densification point was 1.64 MJ/m 3 and 2.47 MJ/m 3 for the uniform and graded Schwarz P structures, respectively. There was little difference between the uniform and graded Gyroid samples, and only one structural crack appeared during the compression test. The total absorbed energy for the uniform and graded Gyroid structures was approximately 2.49 MJ/m 3 and 2.51 MJ/m 3, respectively. The results showed that the graded Schwarz P structure absorbed more energy during the compression tests, while energy absorbed in the graded Gyroid structure was close to the uniform Gyroid structure. Furthermore, the relationship between energy absorption and compressive stress was determined and the abnormal characteristics in Gyroid structures were deeply discussed. Graphical abstract: Unlabelled Image Highlights: The idea of designing and fabricating graded triply periodic minimal surface were demonstrated and experimentally confirmed. The energy absorption ability of Schwarz P structures was improved with graded designs. The mechanism of the abnormal mechanical behaviours of both graded and uniform Gyroid structures were deeply discussed.